BRCA1 and BRCA2: two genes, multiple clinical applications - Sh. Kuligina, Ekatherina; Imyanitov, Evgeny N. (Translational Cancer Research; Vol 6, Supplement 6 (August 29, 2017): Translational Cancer Research, 2017)
The discovery of BRCA1 and BRCA2 hereditary breastovarian cancer genes was driven by a well-defined practical purpose: it was expected, that the identification of genetic causes of these diseases will allow to ascertain yet healthy women at-risk, and therefore to reduce cancer mortality through implementing relevant diagnostic and preventive programs. BRCA-associated syndrome is apparently the most common Mendelian genetic disease in humans. Studies on geographic spread of BRCA1/2 mutations revealed a number of founder alleles, thus permitting non-expensive and rapid identification of thousands of mutation carriers in genetically homogenous human communities (1). On the other hand, the majority of patients with suspicion for hereditary breast or ovarian cancer require comprehensive BRCA1/2 testing; exhaustive BRCA1/2 analysis remains complicated even for the time being, as it includes the detection of both small mutations and gross rearrangements across the entire coding regions of these genes (2). BRCA1 and BRCA2 gene alterations appear to be associated with somewhat distinct disease phenotypes, with a plethora of genetic and non-genetic factors modifying their penetrance (3,4). Diagnostic attitudes towards BRCA1/2 mutation carriers continue to evolve, given that some of the BRCAdriven cancers are notoriously difficult to detect at yet manageable stages (5,6).